Validating the Malay Version of Adolescent Sexual and Reproductive Health Knowledge and Attitudes Questionnaires - Gerraint Gillan Ahi; Md Mizanur Rahman; Rafazila Ramli; Rasitasam Safii; Jacey Lynn Minoi; Stephanie Chua Hui Li; Ahmad Sofian bin Shminan; Lee Jun Choi (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Adolescent Sexual and Reproductive Health (SRH) knowledge is crucial for informed decision-making, yet cultural barriers in Malaysia limit open discussions, creating significant knowledge gaps. This study validated the Malay version of the Adolescent SRH Knowledge and Attitudes Questionnaire to address this need. The validation process included expert content review (6 panelists), face validity testing (30 respondents), and psychometric analysis among 100 adolescents in Sarawak. The questionnaire demonstrated excellent content validity as rated by the experts and strong face validity among adolescents. The knowledge domain showed high internal consistency (α = 0.935), while the attitude domain had moderate reliability (α = 0.682), with refinements improving item alignment. The validated questionnaire provides a culturally adapted tool for assessing SRH among Malaysian adolescents, supporting targeted interventions. Future studies should expand validation to diverse populations and the assess longitudinal stability.